ADP1 affects abundance and endocytosis of PIN-FORMED proteins in Arabidopsis - Li, Jieru (Plant Signal Behav, 2014)
Auxin, as a vital plant hormone, regulates almost every aspect of plant growth and development. We previously identified a dominant mutant, adp1-D, displaying loss of apical dominance. We also demonstrated that down-regulation of local auxin biosynthesis in adp1-D was responsible for the bushy phenotype of this mutant. Consistent with the reduction of local auxin biosynthesis, we recently discovered that protein abundance of PIN1, PIN3, and PIN7 was reduced in adp1-D without accompanying transcription level changes. Additionally, subcellular analysis revealed that over-expression of ADP1 inhibited endocytosis of PIN proteins. Taken together, we conclude that ADP1 regulates plant architecture through the fine-tuning of local auxin biosynthesis and through post-transcriptional regulation of auxin transporters.